GAMBARAN UMUR IBU, USIA KANDUNGAN, DAN TINGGI IBU TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI WILAYAH PUSKESMAS 1 GIANYAR BALI TAHUN 2015 - Ahmad Syahir (DiscoverSys Inc., 2016)
Low weight Birth Infant (LWBI) is seen as a problem in UPT Kesmas Gianyar 1. In 2013 there are 39 cases of LWBI and 3 of them passed away.In 2014 there are 25 cases LBWI, 13 boys, 12 girls and 4 of them passed away.In 2015 there are 10 cases until February 2015. High prevalence of LBWI are cause by multifactor such as (age, early or late marriage, height, number of child and number of pregnancy), social economic, pregnancy factor (pregnancy aterm/preterm, infection of fetus and ANC) and intake of balance nutrition.This study is using case control method with cases group (<2500g) dan control group (>2500g). All sample are taken from March 2014 until April 2015 at UPT Kesmas Gianyar I. Total cases group are 26 samples and and total control group are 52 samples.Total sampling method for cases group and accidental sampling method are used for control group.Sample that are less than 20 years old and more than 35 years old have the probability 3.40 times or 77% for having LBWI compare to group of sample 20 until 35 years old. Pregnancy period less than 37 weeks have more probabilty 11.40 times or 91% for having LBWI compare to samples of pregnancy more than 37 weeks. Height of sample less than 145 cm have more probabilty 1.55 times having LBWI or 60% chance for having LBWI compare to samples height more than 145cm.